2010
DOI: 10.1177/1367493510382243
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ attitudes to smoking and passive smoking and their experience of the tobacco preventive work in child health care

Abstract: The purpose of this study was to describe parents' attitudes to smoking and their experience of the tobacco preventive work in antenatal care and in Child Health Care (CHC) in Sweden. A population based survey in which 62 percent of 3000 randomly selected parents with 1- and 3-year-old children answered a questionnaire. Fifty-six percent stated that smoking was registered in the health record of the child yet no further discussion regarding passive smoking took place. The parents' educational level and smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
(35 reference statements)
0
10
0
1
Order By: Relevance
“…Carlsson et al [24] identified that parents’ education level and smoking status are related to their attitudes toward, and risk awareness of, parental smoking. However, only one question in each actually measured attitudes and risk awareness, and another question related to attitude was directly targeted at smokers who might induce misinterpretation for nonsmokers to answer.…”
Section: Introductionmentioning
confidence: 99%
“…Carlsson et al [24] identified that parents’ education level and smoking status are related to their attitudes toward, and risk awareness of, parental smoking. However, only one question in each actually measured attitudes and risk awareness, and another question related to attitude was directly targeted at smokers who might induce misinterpretation for nonsmokers to answer.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that parents want to have and read information concerning children and their health [21] and migrants want written information both in Swedish and in their native language [57]. Thus booklets written in parents’ native languages may help assist them in their decision to change their smoking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was carried out with an interactive approach where the researcher was given access to an understanding based on the participants’ own perspectives, both from the CHC nurses and the parents [30]. The results from the two earlier studies [20,21] formed the basis for the intervention which was designed to reduce children’s ETS exposure in their homes in “high risk areas”. In order to successfully communicate with parents with different backgrounds, the dialogue between nurses and parents needed to be improved, and in order to make this improvement, different evidence based components were combined in an “intervention bundle”.…”
Section: Methods and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates that CHC nurses had a positive attitude to tobacco prevention [9]. However, results indicated that parents were not satisfied with tobacco prevention in CHC and expressed a wish to have a dialogue with the CHC nurse about how they could protect their child from ETS exposure [10]. …”
Section: Introductionmentioning
confidence: 99%